MASOFAVIY O‘QITISH TIZIMINI RIVOJLANTIRISHNING KONSEPTUAL ASOSLARI - Usarov Jabbor Eshbekovich; Eshnaev Nortoji Jumaevich; Bozorov Xasan Nematovich (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2020)
This article discusses the history of distance learning, its role in society, the experience of foreign countries, the analysis of statistical data, the possibility of teaching in the education system and the mechanism of its implementation